Treatment of Recurrent or Metastatic Uterine Adenosarcoma. (28th December 2017) - Nathenson, Michael J.; Conley, Anthony P.; Lin, Heather; Fleming, Nicole; Ravi, Vinod
Abstract : Purpose . This study retrospectively evaluated overall survival (OS) by treatment of recurrent or metastatic uterine adenosarcoma including surgery, radiation, chemotherapy, and hormonal therapy and evaluated OS and progression-free survival (PFS) after 1st line systemic chemotherapy. Methods . 78 patients with recurrent or metastatic adenosarcoma comprised the study population. The Kaplan-Meier method was used to estimate OS and PFS. The log-rank test was performed to test the difference in survival between groups. Results . Median OS from diagnosis of recurrent or metastatic disease was 1.8 yrs. OS was influenced by pathology on recurrence, p =0 .035 . Median OS differed by surgery for 1st recurrence 26.3 months versus 15.1 months. OS was not influenced by chemotherapy, p =0 .58, palliative radiation, p =0 .58, or hormonal therapy, p =0 .15 . The response rate (CR + PR) per RECIST 1.1 for chemotherapy was 31.2% for doxorubicin-based regimens and 14.3% for gemcitabine/docetaxel. OS since 1st line chemotherapy was not significantly different among chemotherapy regimens. However, the median PFS was superior for doxorubicin/ifosfamide (15.4 months) compared to gemcitabine/docetaxel (5.0 months), platinum-based regimens (5.7 mo), or other doxorubicin-based regimens (6.5 months). Conclusion . These results suggest that surgery is an important treatment modality for recurrent or metastatic uterine adenosarcoma, and the most effective chemotherapeutics are doxorubicin/ifosfamide and gemcitabine/docetaxel.